Tooth enamel EPR dosimetry: optimization of EPR spectra recording parameters and effect of sample mass on spectral sensitivity - Zhumadilov, Kassym; Ivannikov, Alexander; Skvortsov, Valeriy; Stepanenko, Valeriy; Zhumadilov, Zhaxybay; Endo, Satoru; Tanaka, Kenichi; Hoshi, Masaharu (Journal of Radiation Research. http://jrr.jstage.jst.go.jp, 2005)
conditions were optimized. The uncertainty of dose determination was obtained as the mean square deviation of doses, determined with the use of a spectra deconvolution program, from the nominal doses for ten enamel samples irradiated in the range from 0 to 500 mGy. The spectra were recorded at different microwave powers and accumulation times. It was shown that minimal uncertainty is achieved at the microwave power of about 2 mW for a used spectrometer JEOL JES-FA100. It was found that a limit of the accumulation time exists beyond which uncertainty reduction is ineffective. At an established total time of measurement, reduced uncertainty is obtained by averaging the experimental doses determined from recorded spectra following intermittent sample shaking and sample tube rotation, rather than from one spectrum recorded at longer accumulation time. The effect of sample mass on the spectrometer’s sensitivity was investigated in order to find out how to make appropriate corrections.
Keywords: EPR spectroscopy; tooth enamel; dose determination; Research Subject Categories::MEDICINE